O conhecimento matemático para o ensino e os "por quês" dos alunos - Serra, Rodrigo Donizete (2018)
The present paper refers to a research developed at the Master’s in Education Program from São Carlos Federal University (UFSCar) – Campus Sorocaba-SP, Brazil, and it is linked to the Observatory of Education Program (OBEDUC) in the field of mathematics education. The objectives of the research are to understand which knowledge is mobilized for mathematics teaching from the reflection on the students’ ‘whys’, elucidate what composes the knowledge for mathematics teaching, and reveal, based on students’ ‘whys’, the formative potentialities for mathematics teachers. The methodological procedure was conducted in two stages. During the first stage 105 ‘Whys’ were produced together with high school students, in the city of Campinas- SP, in three different schools. These data were categorized in the field of classic mathematics and on a second stage they were taken to teachers from elementary education on two focal groups, in two groups of studies and researches: GEPRAEM from UFSCAR - Campus Sorocaba and GEPEMAI from UNICAMP - in the city of Campinas-SP. They were based on articles about this theme written by Lorenzato (1993), Barbosa (2011), and Moriel and Wielewski (2013) and on the conception of Mathematical Knowledge for Teaching (MKT), developed by Ball, Thames, Phelps, (2008). It is possible to understand through the accounts of Focal Groups (FG) members the importance of these ‘Whys’ as elements that awake investigation and reflection about the practice, potentializing continuing education, and possibly collaborating to expand the MKT of mathematics teachers and resizing their conceptions about the knowledge of contents and didactic knowledge of contents.